2017
DOI: 10.1371/journal.pone.0172398
|View full text |Cite
|
Sign up to set email alerts
|

Elderly fall risk prediction using static posturography

Abstract: Maintaining and controlling postural balance is important for activities of daily living, with poor postural balance being predictive of future falls. This study investigated eyes open and eyes closed standing posturography with elderly adults to identify differences and determine appropriate outcome measure cut-off scores for prospective faller, single-faller, multi-faller, and non-faller classifications. 100 older adults (75.5 ± 6.7 years) stood quietly with eyes open and then eyes closed while Wii Balance B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 35 publications
(61 reference statements)
7
90
0
5
Order By: Relevance
“…The increase in the CoP mean velocity (as observed in the present study, Figure 2B) has been considered an important predictor of the risk of falls in the elderly [26,43]. In addition, high levels of anxiety can modulate oculomotor control [47] and influence orthostatic postural control in young adults [48] as in the elderly [49], partially explaining the results observed in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increase in the CoP mean velocity (as observed in the present study, Figure 2B) has been considered an important predictor of the risk of falls in the elderly [26,43]. In addition, high levels of anxiety can modulate oculomotor control [47] and influence orthostatic postural control in young adults [48] as in the elderly [49], partially explaining the results observed in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, a posturography study using the WBB showed that changes in CoP (increased SD and MV) may predict the risk of falls in the elderly [43]. The FoF consists of a psychoemotional response to a previous event, which can modulate the reflex activity of the neuromuscular spindle [18] and influence the anticipatory postural control [19,20] in threatening situations (elevating participants at different heights) [11][12][13][14][15]44] or functional (unipodal and bipodal supports) [16,17] situations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on fall-risk predictors have recognised the necessity for multiple features and non-linear algorithms in classifying fall-risk by exploring the potential of machine-learning to create effective classification models (25)(26)(27)(28)(29). The majority of these studies have focused on dynamic movement analysis to predict elderly fall-risk (25,26), while the presence of a thorough feature selection process has been lacking with one study of note using principal component analysis (30).…”
Section: Introductionmentioning
confidence: 99%
“…The Romberg Quotient is the ratio of postural sway with eyes-closed and eyes-opened and measures how reliant a person is on vision to maintain balance. The Romberg Quotient has been used to classify fallers, non-fallers, and multiple fallers [26].…”
Section: Fall Risk Assessmentmentioning
confidence: 99%
“…In bipedal locomotion, this represents the average of the pressures acting on the ground contact area, weighted by the ground reaction under each foot [19]. COP-based measures are commonly used to determine fall risk in posturography [18,26].…”
Section: Centre Of Pressurementioning
confidence: 99%